Comparative Measurements on Loudspeaker Distortion: Current vs. Voltage Control - MERILÄINEN, Esa (Archives of Acoustics, 2017)
Modulation and harmonic distortion produced by ordinary moving-coil direct-radiator drive units are measured under current control and voltage control. A realistic two-tone test signal is used to investigate the detrimental effect of the voice coil electromotive forces on the voltage-to-current conversion that is critical with voltage control. Dramatic improvements in distortion performance are obtained with current control. Current nonlinearities in voltage-controlled speakers are shown to be the dominant source of modulation and odd harmonic distortions at signal frequencies above the fundamental resonance region. Currents in conductive voice coil formers also seem to be significant sources of distortion; with current control and non-conductive formers, odd harmonics and related modulation products virtually vanished in the upper midrange.